Menyibak Nilai Kearifan Lokal Dalam Ritus Pander Jampa di Desa Pepas, Kec. Gunung Timang: (Ditinjau Dari Perspektif Strukturalisme Claude Levi-Strauss) - Sariyono, Salvianus; Endi, Yohanes (Universitas Insan Budi Utomo, 2025)
Focus of this research is to uncover the value of unity embedded in the Pander Jampa ritual in Pepas Village through Claude Lévi-Strauss's structuralism approach. This ritual is a cultural tradition rich in symbolic and social meaning, collectively performed by the community as a bond of unity among them. Through structural analysis, this ritual is understood as a system of signs that reflects the community's thought structure. The Pander Jampa ritual not only preserves local cultural identity but also reinforces the value of unity amidst diversity. Using Lévi-Strauss's approach, this article reveals that behind the symbolic practices lies a deep structure that reflects the community's way of understanding and maintaining social unity. The local wisdom values inherent in this tradition are equality and justice, togetherness, and solidarity.